An investigation of the implications of the decision to close the abalone fishery and the impacts on abalone rights holders in Kleinmond, South Africa - Neethling, Karin (Department of Environmental and Geographical Science, 2014)
Thesis (M.Phil. (Environmental Management))--University of Cape Town, 2008.